Demonstration of interference patterns by the random walk of particles - Grabec, Igor (Strojniški vestnik, 2021)
Visualization of interference phenomena by Chladni patterns is treated. The formation of the pattern in the Young's double-slit experiment is described by a new model of driven random walk exhibited by particles bouncing on a vibrating surface. In the model the mean length of horizontal displacement is described deterministically by the wave amplitude. The presented example indicates that such formation of interference patterns can take place without any pilot-waves associated to particles. In spite od this, the pheomenon remeinds to formation of interference patterns observed at scattering of particles in quantum mechanics.
Keywords: Chladni patterns; Chladnijevi vzorci; interference phenomena; interferenčni pojav; naključno gibanje delcev; random walk of particles; Youngov poskus; Young's experiment